2009
DOI: 10.1111/j.1399-6576.2009.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcome after drowning in an adult population

Abstract: The outcome is closely related to the patient's clinical status on arrival to the hospital. We have found that submersion time, age, GCS, pupillary reactivity and APACHE II at ICU admission were related to mortality. Further research in prospective studies is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…It is unclear when the absence of pupillary responsiveness to light predicts poor outcome. Small retrospective drowning studies have shown absence of pupillary response in the emergency department or ICU to be associated with poor neurologic outcome [119-123]. While pupillary response may return within hours of resuscitation [118], an absent pupillary response at 24 h is associated with poor neurologic outcome [70, 124, 125].…”
Section: Neuromonitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear when the absence of pupillary responsiveness to light predicts poor outcome. Small retrospective drowning studies have shown absence of pupillary response in the emergency department or ICU to be associated with poor neurologic outcome [119-123]. While pupillary response may return within hours of resuscitation [118], an absent pupillary response at 24 h is associated with poor neurologic outcome [70, 124, 125].…”
Section: Neuromonitoringmentioning
confidence: 99%
“…A composite GCS score ≤ 5 on ICU admission after drowning is associated with poor outcome, however, it is only 75 % specific to detect patients with a poor outcome. Some patients with a GCS ≤ 5 on ICU admission may have intact neurologic survival [122, 123]. …”
Section: Neuromonitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia remains the main predictor of outcome. [21] If the patient survives to the ED, mortality can still be ≥93%, depending on the initial presen ta tion. [5] Table 1 describes the initial clinical findings and the associated mortality rates.…”
Section: Disposition Planningmentioning
confidence: 99%
“…These characteristics may inform strategies to prevent drownings and improve resuscitation efforts. Most epidemiologic studies of drownings are derived from European countries that border oceans and report incidence and mortality statistics, 3,5,[8][9][10][11][12][13][14] with little emphasis on the prehospital characteristics.…”
Section: Ré Sumémentioning
confidence: 99%